2011
DOI: 10.1007/s00296-011-1963-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of liver function tests in scleroderma patients

Abstract: Systemic sclerosis is a clinically heterogeneous, systemic disorder which affects the connective tissue of the skin, internal organs, and the walls of blood vessels. It is characterized by alterations of the microvasculature, disturbances of the immune system and by massive deposition of collagen and other matrix substances in the connective tissue. This study was done to evaluate the frequency of liver disease in patients with scleroderma and, secondarily, to study the frequency of infection of hepatitis B an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“… 6 , 41 Liver abnormalities included primary biliary cirrhosis (PBC), 6 , 41 primary sclerosing cholangitis (PSC), 9 and gallbladder dysmotility. 42 Salem et al 3 reported ALP increasing by 30% and ALT increasing above reference values by 17.5% in SSc patients compared to controls. Salem et al 3 also found that gamma-glutamyl transferase (GGT) trended to be higher in patients with SSc.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“… 6 , 41 Liver abnormalities included primary biliary cirrhosis (PBC), 6 , 41 primary sclerosing cholangitis (PSC), 9 and gallbladder dysmotility. 42 Salem et al 3 reported ALP increasing by 30% and ALT increasing above reference values by 17.5% in SSc patients compared to controls. Salem et al 3 also found that gamma-glutamyl transferase (GGT) trended to be higher in patients with SSc.…”
Section: Discussionmentioning
confidence: 96%
“… 42 Salem et al 3 reported ALP increasing by 30% and ALT increasing above reference values by 17.5% in SSc patients compared to controls. Salem et al 3 also found that gamma-glutamyl transferase (GGT) trended to be higher in patients with SSc. Our study revealed many patients with abnormal LFT by routine screening during follow-up (430 of 674 SSc cases), which seemed higher than in previous reports, although a direct comparison is not possible.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, we found the correlation of decreased serum H‐ficolin levels with active alveolitis in SSc‐ILD. Considering that H‐ficolin is produced in the lung and liver, and that the liver is basically resistant to fibrosis in SSc, H‐ficolin seems to be selectively involved in SSc‐ILD development.…”
Section: Discussionmentioning
confidence: 99%